Naissance de la diplomatie moderne (XIIIe-XVIIe siècles) L'ambassadeur au croisement du droit, de l'éthique et de la politique - Fedele, Dante (Studien zur Geschichte des Völkerrechts, 2017)
The author investigates the birth of modern diplomacy. Drawing on a wide-ranging body of textual materials dealing with the ambassador from the 13th to the 17th century, he analyses how that figure was developed within a complex constantly renewed field of interaction between law, ethics and politics, where theory and practice are intertwined in an unresolved dialectical interaction. The first part examines how the legal status of the ambassador was shaped during the late Middle Ages and how this process influenced early-modern scholarship on diplomacy. The second part investigates how the emergence of the modern State both reinvigorated and reshaped the scholarly approaches to the different themes linked to the figure of the ambassador. The third part proposes an account of how the professional status of the ambassador developed within the examined body of literature. Through the prism of these approaches, diplomacy appears as a foundational matrix of modern political rationality.